2019
DOI: 10.4149/bll_2019_072
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of quercetin and selenium on oxidative stress in endometrial adenocarcinoma cells

Abstract: OBJECTIVE: The effects of quercetin and selenium on oxidative stress in endometrial adenocarcinoma cells are unclear. In this study, the effects of quercetin and selenium on oxidative stress caused by both hydrogen peroxide and UV radiation in endometrial adenocarcinoma cells were examined. METHODS: The viability of endometrial adenocarcinoma cells cultured in vitro and treated with different concentrations of quercetin and sodium selenite was measured using the MTT assay. Malondialdehyde (MDA) levels were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…MDA, as an end-product of lipid peroxidation, may be used as an indicator of oxidative stress that increases in the body after administration of vinblastine. Results also showed that the use of quercetin compound reduced malondialdehyde levels in the bone marrow compared to the group receiving vinblastine, which was similar to the results of previous studies, 34,35 showing that quercetin partially protects blood glutathione and leads to suppression of plasma malondialdehyde levels, as well as nitric oxide metabolites and the production of superoxide anion. Collectively, the results of the present study showed that chronic administration of quercetin in rats caused inhibition of lipid peroxidation.…”
Section: Discussionsupporting
confidence: 88%
“…MDA, as an end-product of lipid peroxidation, may be used as an indicator of oxidative stress that increases in the body after administration of vinblastine. Results also showed that the use of quercetin compound reduced malondialdehyde levels in the bone marrow compared to the group receiving vinblastine, which was similar to the results of previous studies, 34,35 showing that quercetin partially protects blood glutathione and leads to suppression of plasma malondialdehyde levels, as well as nitric oxide metabolites and the production of superoxide anion. Collectively, the results of the present study showed that chronic administration of quercetin in rats caused inhibition of lipid peroxidation.…”
Section: Discussionsupporting
confidence: 88%
“…A previous study showed that quercetin could inhibit human intestinal oxidative stress by reducing ROS production [23]. Quercetin and selenium reduced MDA levels and inhibited oxidative stress caused by hydrogen peroxide and UV radiation in endometrial adenocarcinoma cells [24]. In the liver mitochondria, quercetin treatment decreased the ROS and MDA levels and increased the CAT and glutathione (GSH) levels [25].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, quercetin is able to protect cells against oxidative stress by decreasing the number of reactive oxygen species (ROS) [ 70 ]. Subsequently, signaling pathways induced by ROS which are participating in cancer initiation/progression are inhibited by quercetin [ 70 , 73 ]. In this regard, a great body of research has examined quercetin on different types of cancer.…”
Section: Quercetin Is a Natural Compound With A Variety Of Advantagesmentioning
confidence: 99%